The capabilities and deficiencies of life cycle assessment to address the plastic problem - Miller, Shelie A. (Frontiers in Sustainability, 2022)
Plastic is a ubiquitous material that has caused major environmental impacts. Ecosystem damage from improperly disposed plastic waste is the most visible of these impacts; however, plastic also has less visible environmental impacts throughout its supply chain, as well as resource depletion associated with the lack of circularity of most plastic streams. At the same time, plastic is not unique in possessing severe, often invisible, environmental impacts that occur throughout its life cycle. Life cycle assessment (LCA) is a helpful tool can be used to contextualize the environmental impacts of plastic compared with alternative solutions or material substitutes. LCA can broaden our understanding of the environmental impacts of a product beyond what is the most obvious and visible, taking a comprehensive view that encompasses raw material extraction, manufacturing, transportation, use, and end-of-life. LCA can be used to target specific areas for improvement, understand and evaluate tradeoffs among different materials, and can be helpful to avoid environmental problem-shifting. This review provides an overview of the LCA process and describes the benefits and limitations of LCA methods as they pertain to plastic and plastic waste. This paper summarizes major trends that are observed in prior LCA studies, along with a discussion of how LCA can best be used to help resolve the plastics problem without causing other unintended issues. The life cycle perspective analyzes the environmental impact associated with a specific product, often comparing the environmental impacts of one alternative to another. An alternative perspective analyzes the aggregated environmental impacts of the entire plastic sector, analyzing the full scope and scale of plastics in the environment. Both perspectives provide meaningful data and insights, yet each provides an incomplete understanding of the plastics problem. The comparative LCA perspective and the aggregated environmental impact perspective can complement one another and lead to overall improved environmental outcomes when used in tandem. The discussion highlights that reduced consumption of the underlying need for plastic is the only way to ensure reduced environmental impacts, whereas interventions that promote material substitution and or incentivize shifts toward other kinds of consumption may result in unintended environmental consequences.